1991
DOI: 10.1002/jctb.280510205
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic investigation of penicillin g acylase from a mutant strain of Escherichia coli ATCC 11105 immobilized on oxirane–acrylic beads

Abstract: A B S T R A C T Highly purifiedpenicillin G acylase from a tnutant derivative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 17 publications
2
4
1
1
Order By: Relevance
“…It can be also concluded that 6-APA is a noncompetitive and PAA is a competitive inhibitor. This is in agreement with the results previously reported [12,14,15,25,26]. Jianguo et al [25] determined inhibition constants as K iA = 0.009 M and K iB = 0.013 M for PGA immobilized on poly(vinyl acetate-co-divinyl benzene) beads.…”
Section: Effect Of 6-apa and Paa On The Free And Immobilized Pgasupporting
confidence: 90%
See 3 more Smart Citations
“…It can be also concluded that 6-APA is a noncompetitive and PAA is a competitive inhibitor. This is in agreement with the results previously reported [12,14,15,25,26]. Jianguo et al [25] determined inhibition constants as K iA = 0.009 M and K iB = 0.013 M for PGA immobilized on poly(vinyl acetate-co-divinyl benzene) beads.…”
Section: Effect Of 6-apa and Paa On The Free And Immobilized Pgasupporting
confidence: 90%
“…Therefore, the immobilized enzyme has apparently lower affinity for the substrate than the free enzyme. The increase in K M after immobilization of the enzyme was also reported in literature [13,14,16,24,25]. Jianguo et al [25] reported a K M value of 0.033 M, which is almost the same as the K M value obtained in the present study showing the same affinities for the substrate of the immobilized enzymes.…”
Section: Reaction Kineticssupporting
confidence: 89%
See 2 more Smart Citations
“…Takođe je pokazano i da i slobodnu i imobilisanu PAC inhibira supstrat u višku i oba proizvoda reakcije, pri čemu je 6-APA nekompetitivni, a PAA je kompetitivni inhibitor. Ovi rezultati se slažu sa rezultatima objavljenim u literaturi [29,50,244,246,247]. Za imobilisanu PAC na poli(vinil acetat-ko-diviil benzen) česticama dobijene su vrednosti za K iA i K iB od 0,009 mmol/cm 3 i 0,013 mmol/ cm 3 , redom [246].…”
Section: Ispitivanje Stabilnosti Imobilisanog Enzima Nakon Višekratneunclassified